Pass finals - Smith, Geoff; Carty, Elizabeth; Langmead, Louise (Pocket essentials, 2013)
Pass Finals is a notes-style summary of the key facts to know for the diagnosis and management of important diseases. The book relates to Kumar & Clark's Clinical Medicine, and it's synoptic approach is intended to help time-poor students with revision for final exams in medicine. Information is presented as bullet point lists and short summaries. There are also practice self-assessment questions at the end of each chapter, with explanatory answers at the end of the book. Focuses on the most important medical specialities, including cardiology, neurology, GI, and rheumatology.